Implementation Of The Learning Cycle 5E Learning Model To Improve Student The Learning Outcomes Of Class XI Student on The Reaction Rate Material at The Ambon Hight School - Nurgaib Karepesina (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2022)
Research has been carried out on the application of the 5E learning cycle learning model to improve student learning outcomes in the subject of reaction rate in class XI SMA Christian Passo Ambon. The type of research used is descriptive type. The subjects in this study were 24 students of class XI IPA at SMA Kristen Passo Ambon. From the results of the analysis of the data obtained, it shows that all students have achieved the completeness criteria for cognitive aspects, namely 5 students (20.83%) with very good qualifications and 19 students (79.17%) with good qualifications. The affective aspect is 17 students (70.83%) with very good qualifications and 7 students (29.16%) with good qualifications. And psychomotor aspects, namely 17 students (70.83%) with very good qualifications and 7 students (29.16%) with good qualifications.